2015
DOI: 10.2500/aap.2015.36.3848
|View full text |Cite
|
Sign up to set email alerts
|

The association of vitamin D, cathelicidin, and vitamin D binding protein with acute asthma attacks in children

Abstract: Vit D deficiency showed a significant relationship to the development of asthma attacks independent of cathelicidin deficiency and other factors associated with the severity of chronic asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 0 publications
2
26
1
2
Order By: Relevance
“…Some case-controlled studies could show the association between vitamin D deficiency and asthma in children. In a study by Arikoglu et al [15], the association between vitamin D deficiency and increased risk for asthmatic attack in children was indicated. In this regard, the mean serum level of vitamin D in the asthma attack group was significantly lower than that of the controlled asthma group.…”
Section: Discussionmentioning
confidence: 99%
“…Some case-controlled studies could show the association between vitamin D deficiency and asthma in children. In a study by Arikoglu et al [15], the association between vitamin D deficiency and increased risk for asthmatic attack in children was indicated. In this regard, the mean serum level of vitamin D in the asthma attack group was significantly lower than that of the controlled asthma group.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent analysis, vitamin D deficiency was associated with low lung function among obese children with asthma, but not among those of normal weight 58 . Another recent study reported that high BMI was associated with asthma exacerbations among children with low vitamin D, with cathelicidin (an innate immunity polypeptide found in macrophages and neutrophils) potentially playing a mediating role 59 . Omega-3 and omega-6 fatty acids have also been linked to asthma 60 , and fish oil supplementation in early life has been reported to modulate immune responses 61 .…”
Section: Diet and Nutrientsmentioning
confidence: 99%
“…Vitamin D deficiency is a condition that is still being reported at quite high rates all over the world, including developed countries, and it can lead to serious health problems (21). In our study, it was detected that while duration of VD intake is the only factor affecting the serum VD level, insufficient serum VD level is a risk factor related to wheezing.…”
Section: Discussionmentioning
confidence: 57%